Case reportPosterior tibial artery false aneurysm as an early complication after fogarty embolectomy - Capoccia, Laura; Gazzetti, Marianna; Sbarigia, Enrico; Speziale, Francesco (Archives of Medical Science, 2008)
Pseudoaneurysm is a possible complication after Fogarty balloon catheter thrombectomy because of intimal linear or full-thickness tears or disruption of the vessel wall. A 50-year-old woman was admitted with acute severe ischaemia of the lower extremities due to bilateral embolic common femoral artery occlusion so an embolectomy was performed under local anaesthetics. On the third post-operative day the patient complained of increasingly severe pain in her left calf with reduced dorsiflexion. A pseudoaneurysm was diagnosed and through a medial approach it was opened and the posterior tibial artery was reconstructed by a great saphenous vein autograft interposition.